1995
DOI: 10.1002/pola.1995.080331314
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of polyyne polymer containing nickel in the main chain

Abstract: The synthesis of the nickel dialkynyl complex Ni(CCC6H4CCH)2(PPh3)2 and of the corresponding polyyne polymer containing nickel in the main chain [Ni(PPh3)2CCC6H4CC]n are described and discussed. A new mixed solvent system DMSO/HNEt2 and homogeneous step‐wise condensation method used for their synthesis are presented for the first time. The Ni‐polyyne polymer obtained is dark yellow powder and soluble in THF or CH2Cl2. Its M̄w is about 104, and the MWD is less than 2. Both the prepared complex and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Basically, the same dehydrohalogenation protocol as for the polyplatinynes can also be applied for the corresponding Pd IIor Rh I -containing polyynes; 455,[457][458][459][460][461] however, the improved methods reported by the Lewis 462 and Lo Sterzo [463][464][465] groups were found to be of much wider scope (Scheme 36). Polyynes of metals of the groups 8 and 9 (i.e., Fe II , 466,467 Ru II , 466,[468][469][470][471] Os II 466 and Rh II 462,472 ) as well as of group 10 (in particular, Pd II and Ni II ) 473,474 can be obtained using metathesis of SnMe 3activated aromatic diacetylides. In general, Hagihara's protocol cannot be applied to, e.g., Ni II , due to the instability of the dihalo complexes in the presence of amines and dialkynyl species under oxidizing conditions.…”
Section: Metallo-supramolecular Polymers Based On Coordinative Bindingmentioning
confidence: 99%
“…Basically, the same dehydrohalogenation protocol as for the polyplatinynes can also be applied for the corresponding Pd IIor Rh I -containing polyynes; 455,[457][458][459][460][461] however, the improved methods reported by the Lewis 462 and Lo Sterzo [463][464][465] groups were found to be of much wider scope (Scheme 36). Polyynes of metals of the groups 8 and 9 (i.e., Fe II , 466,467 Ru II , 466,[468][469][470][471] Os II 466 and Rh II 462,472 ) as well as of group 10 (in particular, Pd II and Ni II ) 473,474 can be obtained using metathesis of SnMe 3activated aromatic diacetylides. In general, Hagihara's protocol cannot be applied to, e.g., Ni II , due to the instability of the dihalo complexes in the presence of amines and dialkynyl species under oxidizing conditions.…”
Section: Metallo-supramolecular Polymers Based On Coordinative Bindingmentioning
confidence: 99%
“…A nickel catalyst Ni(C'CO OC'CH) 2 (PPh 3 ) 2 (NiOC) was prepared by procedure in the literature. 13 Synthesis of (PDEB) is as follows. A solution of p-DEB (378 mg, 3 mmol) and NiOC catalyst (25 mg, 0.03 mmol) in 2.5 mL mixed solvents (1,4-dioxane/toluene ϭ 1 : 1 volume ratio) stood at 25°C under N 2 for 6 h. A brown solution was obtained, then precipitated in methanol, filtered, washed with methanol, and dried under vacuum at room temperature for 24 h, giving an orange powder with about 70% yield and molecular weight (M w ) of ϳ 3000 -5000, which was used for the preparation of humidity sensors.…”
Section: Synthesis Of Pdebmentioning
confidence: 99%
“…trans-Bis(triphenylphosphine) dichloronickel, NiCl 2 (PPh 3 ) 2 was prepared as previously reported. 7 trans-Bis(tri-n-butyl-phosphine) dichloronickel, NiCl 2 (PBu 3 ) 2 , was prepared from the reaction of NiCl 2 ⅐ 6H 2 O with tri-n-butylphosphine (PBu 3 ) in an ethanol solution at room temperature to give the product as purple-red crystals in 88% yield 9 .…”
Section: Methodsmentioning
confidence: 99%
“…2,3 Synthesis of metal-polyyne polymers, O[OML 2 OC'COROC'CO] n O (MAPt, Pd, Ni; LAPBu 3 , PEt 3 , PMe 3 ), was developed by Takahashi and his coworkers, 4 -6 and their nonlinear optical (NLO) properties were investigated by Frazier et al 2 We recently reported the synthesis of nickel-polyyne polymer, O[ONi(PPh 3 ) 2 OC'COC 6 H 4 OC'CO] n O, in which triphenylphosphine (PPh 3 ) ligands are attached to nickel atoms. 7 By comparison with the analogue-containing PBu 3 ligands, the nickel-polyyne polymer with PPh 3 ligands would be expected to exhibit large optical nonlinearity based on their different electron characteristics. However, their solubility in common organic solvents are unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%